Electronic Properties of Complex Self‐Assembled InAs Nanowire Networks. (22nd March 2016) - Heedt, Sebastian; Vakulov, Daniil; Rieger, Torsten; Rosenbach, Daniel; Trellenkamp, Stefan; Grützmacher, Detlev; Lepsa, Mihail Ion; Schäpers, Thomas
Abstract : Electrical transport in epitaxially merged InAs nanowire junctions and nanowire networks is investigated. Single‐crystalline zinc blende regions form at the L‐ and T‐shaped nanowire links. The impact of the junction regions on electrical transport is examined at room temperature and at cryogenic temperatures. The cross configuration is utilized to compare transport properties extracted from the Hall effect and field‐effect transistor characterizations.